Contributing to the Aggregated Expression of Environmental Damage by Air Pollution - Sekerka Bohuslav; Obršálová Ilona; Lešáková Petra (WSEAS Press, 2015)
This article describes one of the possible approaches to the calculation of the pollution and its summary indicator. But, the suggested total indicator of pollution needs a correction according to the bias. This correction is described in this paper on chosen example. The aim is to separate the total pollution into aggregates indicator of material and aggregates indicator of indicator of pollution per unit of quantity of emissions. An indicator of pollution is possible to separate into two different aspects. It is possible to define pollution indices and the indices for quantity. The article presents the process and outcome on real data of air pollution in the Czech Republic.
Souhrnné vyjádření škod na životním prostředí v důsledku znečišťování ovzduší
Keywords: Environmental Damage; Level of Air Pollution; Price Level; Total Value of Pollution; Environmentální škody; úroveň znečištění ovzduší; celková hodnota znečištění